Total Induced Vertex Stress in Barbell-Like Graphs - Shiny, Joseph; Kok, Johan; Ajitha, V. (IndoMS, 2021)
This paper introduces new parameters called induced vertex stress and total induced vertex stress in G, respectively. For graphs G and H, aspects of the maximum and minimum total induced vertex stress that can be obtained by 1-edge addition and 2-vertex merging are discussed.